The Use Spinach Extract in Acehnese Noodles, Canai Bread, and Jala Bread - Hassan, Rayyani; Yuliantoro, V. Nonot (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2023)
The purpose of this research is to make the innovation of spinach extract in the manufacture of Acehnese noodles, canai bread, and jala bread which are typical Acehnese dishes. This research use organoleptic test with 4 indicators namely; texture, color, aroma, and taste. The results of organoleptic test for hedonic test was liked and for hedonic quality test was good quality both limited panelist assessment and consumer panelists. The society will have new knowledge about how to use spinach extract in processing Acehnese cuisine so that this research can be an inspiration for further research. This innovative product brings food from the province of Aceh where there are several cultures from Aceh which are known to use various kinds of spices that are rarely used in cooking in general and also the author tries to evoke and introduce more deeply to the public.